Influence of temperature and diffusion on aerobic granular sludge for municipal wastewater treatment : experimental and modeling studies - ARAÚJO, Julliana Melo Pinheiro de (2022)
Aerobic granular sludge (AGS) has been widely used in recent decades as an alternative to conventional activated sludge systems for treating domestic sewage. AGS increases biomass retention and sedimentation and enables the simultaneous removal of nutrients and organic matter, making it applicable to a wide range of wastewater types, temperatures, and reactor scales, as evidenced in the literature. However, previous studies investigating the roles of engineering parameters such as volumetric organic load, temperature, and hydraulic retention time in the granulation process in AGS systems show yet no consensus, hindering the development of a precisely predictable system. In this context, the mathematical modeling of these systems may provide valuable insights for a more comprehensive understanding of microbial biochemical conversions in AGS systems. Hence, this work investigates the influence of temperature, cycle configuration, and influent composition in sequencing batch reactors (SBR) systems with AGS of different scales, focusing on understanding sensitive parameters through mathematical modeling. For this purpose, four different methodological strategies were used. Initially, two different cycle configurations in a pilot-scale (PS) SBR (115 L) were used to cultivate AGS without inoculum at approximately 30 °C. Data from these experiments were then used to implement and calibrate the biofilm model proposed by Wanner and Gujer (1986) associated with the activated sludge model n° 3 (ASM3 – GUJER et al., 1999). The model calibration showed high sensitivity of diffusion-associated parameters such as boundary layer thickness. To assess these results, we analyzed diffusion, boundary layer thickness, as well as the presence and size of aerobic/anaerobic layers from O2 micro-profiles using granules (1.4- 2.0 mm diameter) collected from two lab-scale (LS) SBR (9.1 and 11.2 L) operated at 20 and 30 °C. The LS reactors were also monitored to investigate the influence of temperature on AGS formation, morphology, and stability. This approach to model implementation enabled the description of a non-steady state AGS system performance related to solids and COD removal. However, it could not capture the complexity of nitrogen removal processes in AGS (under different redox conditions) by assuming a single diameter for all granules. The temperature, in turn, was a primary factor in determining AGS stability, formation, and morphology in the LS reactors. Granules formed at 30 °C (LS) were larger, more compact, and considerably more stable against system disturbances. In addition, a prolonged anaerobic phase or the insertion of air pulses during slow feeding were configuration strategies for SBR cycles that improved the granulation process. The wastewater composition directly affected microbial diversity and system performance, with lower efficiency observed when lower loads were applied. Finally, implementing mathematical models in non-steady-state systems allowed us to analyze the influence of setting fixed parameters, with the number of granules and boundary layer thickness among the most sensitive parameters.